Single Leg Speed Hop Pengaruh Single Leg Speed Hop Terhadap Daya Ledak Otot Tungkai Pada Pesilat - Achwan Achwan; Siti Najiahtul Hasanah; Ari Sudarsono (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
ABSTRACT Background: The explosive power of leg muscle is the ability to exert maximum power in the shortest possible time. Muscle explosive power is important for a fighter in locking, swinging, dropping, punching, kicking and avoiding attacks from unexpected angles and directions. Ways to increase muscle explosive power include plyometric training and one of them is single leg speed hops. Research Objectives: To determine the effect of single leg speed hop pliometric exercises on increasing the explosive power of limb muscles in pesilat members at SMPN 1 Parung. Research Methods: The design of this study was quasi-experimental with "two-group pretest-posttest" with a sample of 28 people selected by purposive sampling divided into two groups, namely the treatment and control groups. Measurement of leg muscle explosive power using the Standing Long Jump Test. Results: The results of the independent t-test obtained a p-value of 0.011 (p<0.005), so Ho is rejected, which means that there is a significant effect on single leg speed hop plyometric exercises. Conclusion: There is an effect of single leg speed hop plyometric exercise on increasing the explosive power of the leg muscles of the members of SMPN 1 Parung. Keywords: The Explosive power leg muscle; Plyometric Exercises; Single Leg Speed ​​Hop; Martial arts